Temazcales o baños de vapor en la región de Puebla-Tlaxcala (México): Elementos para un inventario de la cultura material del espacio rural - Tyrakowski Findeiss, Konrad (Revista Española de Antropología Americana, 2007)
At the Highland of Mexico the temazcal or Mexican bathing-house is part of the traditional cultural heritage from pre-Spanish times. Once as a suspect element distrustfully pursued by the colonial administration of the State as well as of the Church, the bath has still at colonial times developed into an important element of the infrastructure of villages and also in Puebla, the capital of the region. Still today it is in various forms widespreads in the rural settlements, though in the process of modernization it is slowly but increasingly displaced by urban ways of living.